A comparative analysis of the role of traditional and modern community-based organizations in promoting community development in Ogoniland, Nigeria. (13th June 2016) - Okeke-Ogbuafor, Nwamaka; Gray, Tim; Stead, Selina Marguerite
Abstract: Given the failure of top-down initiatives to bring about community development (CD) in many developing countries, attention is switching to bottom-up approaches, one of which is to use community-based organizations (CBOs) as the conduit through which CD may be achieved. This paper compares the effectiveness of traditional CBOs and modern CBOs in fostering CD in eight communities in Ogoniland, Nigeria, where there is a long history of neglect and underdevelopment. The paper was based on extensive fieldwork carried out in eight Ogoni communities during 2013–2014, which involved 101 telephone interviews with residents, 67 face-to-face key informant interviews, 189 survey questionnaires, and 3 focus groups discussions. The two main conclusions reached by this paper are that despite some praise expressed by respondents for their CBOs, the fashionable belief that CBOs are strong agents of bottom-up CD is not borne out by this study; and there is little difference between respondents' evaluations of the contributions to CD made by modern CBOs and the much vaunted traditional CBOs.